ANALYSIS OF ECONOMIC PERFORMANCE OF TRADE COMPANIES IN SERBIA - Lukić, Radojko (Poslovna ekonomija, 2023)
The issue of analysis of economic performance in commercial enterprises in this paper is investigated from the angle of the impact of labor process factors (fixed, working capital and human capital) on profitability and efficiency, on the example of trade enterprises in Serbia. performance. The economic performance of trade companies in Serbia is significantly affected by fixed and working capital. The impact of human capital is moderate. In the future, in order to improve the economic performance of trade companies in Serbia, it is necessary to more efficiently manage human capital through training, salary, improvement of managerial position, compensation.